(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Being a woman in this predominantly patriarchal world is as difficult as it is impossible. The female of the human species is never a woman alone. She must be something else before being that- either a mother or a daughter or a wife or, with a very limited chance of acceptability, a beloved. Seldom has the male been troubled by the predicament which has always beset his female counterpart. He does not need to be someone’s son or husband for an identity. Now, a woman just can’t be a woman alone. This has been the misery of female existence since the beginning of civilization. Even literature, to a great extent, can be accused of forwarding stereotyped images of womenfolk. Manju Kapur in her novel Difficult Daughters breaks the confines of this historical prejudice when her female characters trespass their well-defined social roles. This paper intends to present a study of the novel which takes the reader deep into the complex world of female psychology. Her ladies stand tall and emerge as social outlaws but on the other hand, while moving about from kitchen to the backyard inside the for walls of the house, they appear as mere social archetypes.